Los acentos de la crisis en las voces de la migración (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
Migration throughout the history of humanity undoubtedly refers to the notion of crisis, since it is a demographic phenomenon that is determined by and, at the same time, is a determinant of profound changes of an economic, political and social nature. The crisis is thus manifested in its causes and consequences, at a collective and individual level. Different critical paradigms have questioned the hegemonic narratives on migration, trying to subvert the representations that construct and reproduce in the collective imaginary the idea of the immigrant as a subject that threatens the social order, values and cultural identity of the receiving country, ultimately, capable of triggering a crisis. Also, as a way to contrast this discourse, this paper aims to address the perception and reaction to the crises experienced in the migration process through the narratives of university students of Hispanic American origin living in Italy.
Keywords: Hispanic American migration; crisis; testimony; resilience